2008
DOI: 10.1007/s00421-008-0700-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the distribution of intramuscular current during electrical stimulation of the quadriceps muscle

Abstract: Electrical stimulation is commonly used for strengthening muscle but little evidence exists as to the optimal electrode size, waveform, or frequency to apply. Three male and three female subjects (22-40 years old) were examined during electrical stimulation of the quadriceps muscle. Two self adhesive electrode sizes were examined, 2 cm x 2 cm and 2 cm x 4 cm. Electrical stimulation was applied with square and sine waveforms, currents of 5, 10 and 15 mA, and pulse widths of 100-500 micros above the quadriceps m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
(33 reference statements)
1
25
0
Order By: Relevance
“…Electrically-induced leg muscle fatigue [12] could increase leg discomfort during training and reduce tolerance to NMES. Subcutaneous body fat constitutes a resistance to electrical current in such a way that increasing current intensities may be more challenging in lean patients [13]. Finally, it is possible that the occurrence of a systemic inflammatory response following electrical stimulation could influence the tolerance to NMES but this has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Electrically-induced leg muscle fatigue [12] could increase leg discomfort during training and reduce tolerance to NMES. Subcutaneous body fat constitutes a resistance to electrical current in such a way that increasing current intensities may be more challenging in lean patients [13]. Finally, it is possible that the occurrence of a systemic inflammatory response following electrical stimulation could influence the tolerance to NMES but this has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These include neuronal transmission [ 91,123 ] , pulmonary vascular remodeling [ 111 ] , arterial sclerosis [ 86 ] , and exercise-induced cardiac protection [ 105 ] . Impaired production or bioavailability of nitric oxide leads to endothelial dysfunction and is the root cause of much different cardiovascular pathology including diabetes, hypertension, heart failure, and coronary artery disease [ 92 ] .…”
Section: Nitric Oxidementioning
confidence: 99%
“…Several research studies have investigated factors that affect the distribution of current propagation during electrical stimulation of the knee extensor muscle group [11][12][13][14][15][16][17][19][20][21][22]. It is recognized that increasing the current amplitude may lead to increases in both skeletal muscle motor unit recruitment and evoked torque in a linear pattern [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Maffliuletti et al studied sex-specific response to current distribution and showed that women require lower current amplitude to activate both sensory and motor responses compared to men [15]. This suggests that fat thickness may impact the distribution of current to target skeletal muscle [15,[19][20][21][22]. Leg extension exercise in conjunction with weight lifting has been shown to evoke significant skeletal muscle hypertrophy after SCI [4,9,10].…”
Section: Introductionmentioning
confidence: 99%